Dampak Pandemi Covid-19 terhadap Kinerja Keuangan Perusahaan Farmasi (Studi pada Perusahanaan terdaftar di Bursa Efek Indonesia) - Miftahurrohman (Dinamika: Jurnal Manajemen Sosial Ekonomi, 2021)
The purpose of this study was to determine whether there were significant differences in the financial performance of pharmaceutical companies listed on the IDX from the impact of the Covid-19 pandemic in Indonesia. The research method uses descriptive quantitative methods, the data used in this study is secondary data in the form of financial statements of pharmaceutical companies listed on the Indonesian stock exchange. Analysis of the data using the average difference test paired sample test using the SPSS application, and the measurement of financial performance using the ratio of liquidity and profitability. Liquidity ratio which consists of Current Ratio and Quick Ratio, while Profitability ratio consists of Gross profit Margin, Net Profit Margin, Rate of Return on Assets, and Return on Equity. The results of the study show that there is no significant difference in the financial performance of both the liquidity ratio and profitability of pharmaceutical companies listed on the IDX before the Covid-19 pandemic and during the Covid-19 pandemic.